Conservation of Plasmid Maintenance Functions between Linear and Circular Plasmids in Borrelia burgdorferi - Stewart, Philip E. (American Society for Microbiology, 2003)
The Lyme disease agent Borrelia burgdorferi maintains both linear and circular plasmids that appear to be essential for mammalian infection. Recent studies have characterized the circular plasmid regions that confer autonomous replication, but the genetic elements necessary for linear plasmid maintenance have not been experimentally identified. Two vectors derived from linear plasmids lp25 and lp28-1 were constructed and shown to replicate autonomously in B. burgdorferi. These vectors identify internal regions of linear plasmids necessary for autonomous replication in B. burgdorferi. Although derived from linear plasmids, the vectors are maintained in circular form in B. burgdorferi, indicating that plasmid maintenance functions are conserved, regardless of DNA form. Finally, derivatives of these vectors indicate that paralogous gene family 49 is apparently not required for either circular or linear plasmid replication.